Case report: Endovascular treatment of two scalp arteriovenous malformation cases via direct percutaneous catheterization: A case series - Shi, Yuan; Liu, Peixi; Liu, Yingtao; Quan, Kai; Li, Peiliang; Li, Zongze; Zhu, Wei; Tian, Yanlong (Frontiers in Neurology, 2022)
Background: Scalp arteriovenous malformations (AVM) are rare vascular malformations reported only in small case series. Scalp AVMs usually present with symptoms including headache, tinnitus, epilepsy, cerebral ischemia and necrosis of scalp which can cause functional, cosmetic, and psychological problems. There are many difficulties in the treatment of scalp AVM because of its complex characteristics of vascular anatomy, nonuniform structure and intracranial-extracranial anastomosis. Case Description: To illustrate the endovascular treatment of scalp AVM via direct percutaneous puncture while traditional arterial and venous approach were not available. In this report, access was obtained through direct puncture of the enlarged frontal vein. Onyx-18 was injected through microcatheter to occlude draining veins, fistulous connection, and the feeders. An 18-guage indwelling needle was inserted into draining veins directly. Postembolization angiography demonstrated complete sAVM occlusion immediately and no non-targeted embolization. At one-year follow-up, no procedure-related complications and evidences of recurrence were observed. Conclusion: The technique of endovascular embolization via direct percutaneous puncture approach is safe, rapid and effective for specific sAVM. Treatment options should be made in terms of size, vascular anatomical characteristics of the lesions, patient’s preference, cosmetic factors, and available expertise.